Le Roman Graphique comme support de l’évaluation remédiative - Tereza De Almeida; Bernard De Giorgi (Cahiers d’Études Romanes, 2018)
The present paper explores various issues related to the use of the graphic novel as an educational tool, within the paradigms of formative assessment, through an experiment carried out in English and Portuguese at Aix-Marseille University. In a graphic novel, linguistic phenomena can be studied in a narrative context, and more easily memorized thanks to iconography. Since the graphic novel is mainly the autobiographical expression of a given space and time, it seems natural to use – besides active learning methods – a strategy based on a comparison between what can be regarded as the norm and various speech registers which are to be found in abundance in this medium, such as oral discourse and dated expressions.